Upaya Meningkatkan Kemampuan Literasi dan Numerasi pada Pembelajaran IPAS dengan Model Problem Based Learning di Kelas IV SDN Tambakrejo 01 Semarang - Baeti, Latifah Nur; Mushafanah, Qoriati; Arfilia Wijayanti; Arum Asmawati (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
This study aims to improve reading literacy and numeracy skills using the Problem Based Learning (PBL) learning model in class IV of SDN Tambakrejo 01 Semarang in the science subject matter. Classroom Action Research (CAR) was carried out in 3 cycles using qualitative-quantitative methods. Data collection for this study was obtained from the results of observations, interviews, documentation, and tests. The results of the study showed an increase in the average reading literacy and numeracy skills in science learning, especially in social sciences from cycle 1, cycle 2, and cycle 3. The results of the percentage test in the last cycle, namely cycle 3, the average literacy ability increased to 77.7% with a high category and for numeracy skills by 81.40% with a very high category. This proves that the Problem Based Learning learning model is effective in improving literacy and numeracy skills in science learning, especially in social sciences.